THE INFLUENCE OF ORGANIZATIONAL CULTURE, WORK COMMITMENT AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE (CASE STUDY OF PT. BANK RAKYAT INDONESIA TBK OFFICE OF THE SARAPUNG MANADO BRANCH) - Ni Putu Meydela Suarjana; Olivia S. Nelwan; Imelda WJ Ogi (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This study aims to see the influence of Organizational Culture, Work Commitment and Job Satisfaction on Employee Performance. This analysis uses independent variables, namely Organizational Culture, Work Commitment and Job Satisfaction. The dependent variable is Performance. The sample of this research is the employees of Bank BRI, Sarapung Branch, Manado, North Sulawesi. Sampling was done by saturated sample method. Data collection was carried out by distributing questionnaires directly to 60 employees. The statistical method uses multiple linear regression analysis, with the T test and F test. The results of this study indicate that the influence of organizational culture partially has a positive and significant effect on employee performance, work commitment partially has a positive and significant effect on employee performance, Job satisfaction partially has a positive and significant effect on employee performance. Organizational Culture, Work Commitment and Job Satisfaction simultaneously have a positive and significant effect on Employee Performance.